The demographic situation and the state of morbidity in the population of the Rivne region over 2013-2017 (Environment & Health, 2020)
Objective: We presented a socio-hygienic assessment of the state and dynamic changes in the demographic situation, incidence and prevalence of diseases among the population of the Rivne region.Materials and methods: Analysis of the incidence was performed on the basis of the data collected in 16 districts, the oblast center and 2 cities of oblast significance over 2013-2017. In the study, we used epidemiological and medico-statistical methods.Results: The systematization and analysis of main data, characterizing the demographic situation in terms of fertility, mortality and natural population growth of the oblast have been carried out. In the context of all regions and 3 cities, the state of general morbidity and mortality in the oblast has been studied by main nosological groups of NCD and the incidence of tuberculosis. The data have been systematized and analyzed in the context of the corresponding age groups of the adult and children's population.Conclusion: In the region in 2013-2017, the birth rates had a steady tendency to decrease from 15.1 in 2013 to 12.4 in 2017. There is an increase of the mortality in children born alive aged under 1 year by 5.2%, which indicates the need to improve the quality of medical care in maternity hospitals. As in previous years, diseases of circulatory system, respiratory system, endocrine system, blood-forming organs and neoplasms are the most common ones among the population of the oblast. By nosological groups in the mortality structure, mortality of circulatory system diseases takes first place (72.4%), of neoplasms takes second place (13.9%), of injuries and poisonings - third place (5.1%), of diseases of digestive system - fourth place (3.1%), of respiratory diseases - fifth place (1.6%).
Keywords: health; noncommunicable diseases; general and primary morbidity; mortality